REGRESS DURCH DIE ABTRETUNG VON FORDERUNGEN IN DER LEHRE DER GLOSSATOREN UND KOMMENTATOREN - Kacprzak, Agnieszka (Zeszyty Prawnicze, 2025)
Recourse through the cession of rights in the doctrineof the Glossators and Commentators This article examines the ideas of medieval jurists (glossators and commentators) regarding cession of rights as a mechanism for recourse. Medieval jurists were confronted with the same question that had already been addressed by their Roman predecessors: how can a person who has discharged another‘s debt be granted the ability to take over the creditor‘s claims against the principal debtor? According to the principles governing the extinction of claims, such claims would normally cease as a consequence of the performance of the obligation. A review of the medieval sources shows that the solution proposed by medieval jurists diﬀers in a crucial respect from the approach adopted by Roman jurists. An examination of the work of Azo and Accursius’ and Bartolus’ glosses demonstrates that their solution was founded on a diﬀerent conceptualization of the surety‘s obligation than that recognized by Roman jurists. This shifh in conceptualization was inﬂuenced by Justinian’s Fourth Novel.